2014
DOI: 10.14319/ijcto.0301.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dosimetric analysis of IMRT and VMAT (RapidArc) in brain, head and neck, breast and prostate malignancies

Abstract: Purpose: Intensity modulated radiotherapy (IMRT) in the recent past has established itself as a gold standard for organs at risk (OAR) sparing, target coverage and dose conformity. With the advent of a rotational treatment technology such as volumetric modulated arc therapy (VMAT), an inter-comparison is warranted to address the advantages and disadvantages of each technique. Methods: Twenty patients were selected retrospectively from our patient database. Sites included were brain, head and neck, chest wall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
4
0
2
Order By: Relevance
“…At this point, the RO often has to choose between different techniques, as illustrated in Figure 3, which compared 3D-CRT and VMAT for the treatment of breast cancer, and Figure 4, which compared VMAT and proton therapy for the treatment of a sacral chordoma. For some cases, the choice is quite easy [78], but in some cases the choice is more difficult. Consider the case of a patient with a tumor completely in contact with the parotid gland; the choice will be between irradiating the target volume completely with the risk of inducing severe late oral dryness or better protecting the parotid gland with a higher risk of local recurrence.…”
Section: Step 4: Medical Validation Of the Treatment Planmentioning
confidence: 99%
“…At this point, the RO often has to choose between different techniques, as illustrated in Figure 3, which compared 3D-CRT and VMAT for the treatment of breast cancer, and Figure 4, which compared VMAT and proton therapy for the treatment of a sacral chordoma. For some cases, the choice is quite easy [78], but in some cases the choice is more difficult. Consider the case of a patient with a tumor completely in contact with the parotid gland; the choice will be between irradiating the target volume completely with the risk of inducing severe late oral dryness or better protecting the parotid gland with a higher risk of local recurrence.…”
Section: Step 4: Medical Validation Of the Treatment Planmentioning
confidence: 99%
“…effect and reducing the radiation treatment period [1][2][3][4][5][6][7][8]. In particular, Huh et al [9] reported that the number of IMRT cases increased significantly by a factor of approximately 18 from 2011 to 2018 owing to the expansion of the national health insurance coverage in Korea.…”
mentioning
confidence: 99%
“…(14). Çalışmada elde edilen MU değerleri literatür ile uyumludur (15). VMAT tekniğinin gantry rotasyonu ve ÇYK hareketlerine bağlı olarak IMRT planlarına göre daha konformal planlar ortaya çıkarabilmektedir (16).…”
unclassified
“…VMAT tekniğinin gantry rotasyonu ve ÇYK hareketlerine bağlı olarak IMRT planlarına göre daha konformal planlar ortaya çıkarabilmektedir (16). Çalışmada incelenen yüksek ve orta izodoz hacimleri, VMAT planındaki 4 yarım ark'tan elde edilen daha fazla açıdan optimizasyon yapabilme kapasitesi ile IMRT plana göre daha düşük izodoz hacimlerine sahiptir (15). Elde edilen planlar için kritik organ dozları karşılaştırıldığında; beyin sapı, sağ lakrimal kese, sol optik sinir ve lens IMRT planları için daha iyi sonuç vermiştir.…”
unclassified